Professional psychology training in the COVID-19 era - Sibulelo Qhogwana; Nokulunga Shabalala; Sarah Uren (University of Johannesburg, 2023)
Professional training programmes were, and continue to be, challenged by the implications of Covid-19. Psychology training programmes in South Africa rely on experiential learning as a cornerstone for developing minimum competencies. Covid-19 restrictions meant that teaching and learning, supervision, and work-integrated learning required reconsideration, shifts and upskilling of trainees and trainers. This was particularly important given the emphasis and value of Experiential Learning Theory in training psychologists. This paper uses collaborative autoethnography to reflect on the challenges, lessons, and future recommendations for the navigation of professional training in psychology in the Covid-19 era and beyond. The key reflections highlight the necessity for hybrid learning contexts in circumstances such as Covid-19. Leadership guidance and students' voices are invaluable assets that could facilitate a comprehensive and inclusive training programme during unprecedented times.